1985
DOI: 10.1002/lsm.1900050105
|View full text |Cite
|
Sign up to set email alerts
|

The biomedical effects of laser application

Abstract: This paper briefly reviews the authors' experimental and clinical use of lasers over a 20-year period, during which laser effects on 15 biological systems were studied. Low-energy laser radiation was found to have a stimulating effect on cells, and high-energy radiation had an inhibiting effect. The application of lasers to stimulate wound healing in cases of nonhealing ulcers is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
344
3
86

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 712 publications
(455 citation statements)
references
References 7 publications
14
344
3
86
Order By: Relevance
“…Such data corroborate the results from other authors who have used LILT during 12 days of tissue repair processes and verified responses from the fibroblastic cells and collagen molecules to the treatment 7,8,[19][20][21][22][23][24][25][26][27][28] . The types of activation ways proposed for the laser, take into account its action over the chromophores situated at the mitochondrias and cell membranes.…”
Section: Discussionsupporting
confidence: 90%
“…Such data corroborate the results from other authors who have used LILT during 12 days of tissue repair processes and verified responses from the fibroblastic cells and collagen molecules to the treatment 7,8,[19][20][21][22][23][24][25][26][27][28] . The types of activation ways proposed for the laser, take into account its action over the chromophores situated at the mitochondrias and cell membranes.…”
Section: Discussionsupporting
confidence: 90%
“…Mester observed that in many cases the skin incisions made to implant recalcitrant cells appeared to heal faster in treated animals compared to incisions of control animals that were not treated with light [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Since the report of Mester et al [1]. on low-level laser irradiation of mouse skin to investigate wound healing, many researchers have investigated the influence of laser irradiation on wound healing [1][2][3][4][5], improvement of microcirculation [6], nerve activation [7], treatment of chronic pain and anti-inflammation [8]. The influence of low-level laser irradiation on activation of salivary gland cells has been also investigated [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of low-level laser irradiation on activation of salivary gland cells has been also investigated [9][10][11][12][13]. Previous investigations showed degenerative and inflammatory changes after helium/neon (He-Ne) low-level laser 4 irradiation, histopathologically [9,10]. On the other hand, another study found no detectable degenerative changes in rat submandibular gland cells after gallium-arsenide (Ga-As) low-level laser irradiation [13].…”
Section: Introductionmentioning
confidence: 99%